Clinical Practice Guidelines for Acute Pulmonary Edema. - Pablo Rodríguez Díaz; Juan José Navarro López; Claudio González Rodríguez; José Manuel Ercia Arenal (Medisur)
Clinical Practice Guidelines for Acute Pulmonary Edema. It has been defined as an abrupt and severe failure of the left ventricular function which causes pulmonary edema or cardiac origin interfering with the normal oxygen exchange at pulmonary level. This document includes a review and update of the main clinical aspects allowing the early diagnosis and immediate therapeutic treatment. It includes assessment guidelines focused on the most important aspects to be accomplished.